2003
DOI: 10.1103/physrevb.67.045405
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelectronic and optical properties of carbon nanotubes

Abstract: Magnetoelectronic and optical properties of carbon nanotubes are, respectively, studied within the sp 3 tight-binding model and the gradient approximation. They strongly depend on the magnitude and the direction of the magnetic field, the nanotube geometry ͑radius and chiral angle͒, and the Zeeman splitting. The magnetic field would lead to the change of energy gap, the destruction of state degeneracy, and the coupling of different angular momenta. Hence there are magnetic-field-dependent absorption frequencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(49 citation statements)
references
References 40 publications
(103 reference statements)
2
47
0
Order By: Relevance
“…This has actually been measured for our SWCNT [13], and is also supported by both theoretical and experimental investigations performed on carbon nanotubes, which have shown that nanotubes may have diamagnetic as well as paramagnetic properties depending primarily on their electronic structure (see e.g., [17][18][19][20][21]). Secondly, the functionalization (either with COOH or with Fe 3 O 4 ) of the carbon nanotubes (which are of mixed chirality, and exhibit both semiconducting and metallic properties) leads to further complications.…”
Section: Resultssupporting
confidence: 87%
“…This has actually been measured for our SWCNT [13], and is also supported by both theoretical and experimental investigations performed on carbon nanotubes, which have shown that nanotubes may have diamagnetic as well as paramagnetic properties depending primarily on their electronic structure (see e.g., [17][18][19][20][21]). Secondly, the functionalization (either with COOH or with Fe 3 O 4 ) of the carbon nanotubes (which are of mixed chirality, and exhibit both semiconducting and metallic properties) leads to further complications.…”
Section: Resultssupporting
confidence: 87%
“…There are a lot of experimental and theoretical studies on optical properties of infinite carbon nanotubes [11][12][13][14][15][16][17][18][19][20][21][22][23]. The experimental measurements [11,12] show that optical excitations from the cross polarized light are very important in understanding absorption spectra, or very useful in identifying electronic structures.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental measurements [11,12] show that optical excitations from the cross polarized light are very important in understanding absorption spectra, or very useful in identifying electronic structures. In this work, the p-electronic optical excitations of finite carbon nanotubes in the presence of the cross polarized light are studied within the gradient approximation [17][18][19][20][21][22]. The dependence of the optical spectral function (AðxÞ) on the length (h), the radius (r), the chiral angle (h), and the magnetic flux (/) is investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their unique electronic and physical properties [11,12], carbon nanotubes (CNTs) may act as a catalyst support, on which nanoparticles may be attached to improve catalytic effect [13,14]. M 2 O 3 /CNT nanocomposites have been prepared through numerous methods, such as chemical deposition, sol-gel, hydrothermal, atmosphericpressure-plasma jet, and electrophoretic deposition [15][16][17].…”
Section: Introductionmentioning
confidence: 99%